A hydroponic system for natural turf that can take extreme wear as an alternative to artificial grass surfaces. Issue 1 (13th May 2022) - Sternberg, Martin
Abstract: Natural grass areas in high‐traffic and stress locations are being converted into artificial grass by inconsistent moisture conditions in root‐zone and poor grass conditions. As an alternative solution to this method, natural grass was planted instead in a washed sand without organic matter and with a constantly moving water table and no overhead irrigation. Water consumption and surface quality after heavy machinery exposure was measured. A significantly increase in the potential for traffic and play was observed, along with water savings of up to 85% compared with normal overhead irrigation amounts for similar surfaces (golf course tees).